Risk Evaluation of Venture Capital in China - Hu, Xiao Rui (2006)
ABSTRACT Under the global and integrated tend of world economic development; high and new technology industry has been of momentous significance for optimizing the industry structure, increasing the national competition in the new country. As an innovative finance investment mechanism, venture capital (VC) would effectively settle the problem of financing defines during the development of high-tech enterprise; rationally dispose the resource advance high-tech achievement to be commercialized marketable and industrialized accelerate the combination of science, technology and finance, activate demand and employment, then promote the whole economic development. The key characteristics of venture capital are high risk and high return. In accordance with economic development practice by distinguishing, appraising, controlling and managing risk taking the minimal cost to reduce unfavourable consequence of risk to the lowest extent to achieve breakeven and increment of venture capital. It is a profoundly vital task ensured venture capital farther developed. Focusing on the issues, this dissertation mainly analyzed the demonstrated risk analysis, evaluation and management of venture capital project on the basis of research situation domestic and abroad. The dissertation explained the definition of venture capital, it studied the function, main stages characteristic of venture capital and the difference of investment mode between normal project investment, bank loan and stock investment, analyzed the participative body, operation process and screen criterion o venture capital had the microeconomic analysis with the transaction cost theory and information asymmetric theory. It explicated the definition of risk, elements and the relation between them, founded the theoretical basis of risk analysis and appraisal, and commented on the criterion and method of risk measurement and the means of risk identification, assessment and evaluation. The dissertation applied system theory to analyze the four characteristic of venture capital. The model of risk evaluation and decision making of venture capital project was framed in the dissertation. The paper explicated the characteristics of venture capital appraisal, discuss the technology, market environment, management and liquidity of venture capital project, offered the basic frame and leading theory of risk evaluation, put forward the multi-factor grey hierarchy comprehensive evaluation model. According to the six principles of appraisal criterion, the paper founded venture capital project risk grey hierarchy comprehensive evaluation index system that consists of five subsystem and forty-eight factors. The united frame included the agency risk and liquidity risk that were ignored previously.